Credit restructuring for micro, small and medium enterprises (MSMEs) affected by Covid-19 at PT.Bank Bengkulu (KCP Padang Jaya study) - pratama, yudha; Afandy, Chairil (Institute of Computer Science (IOCS), 2023)
Credit restructuring is an effort by the government and the Financial Services Authority (OJK) to help Micro, Small and Medium Enterprises (MSMEs) affected by Covid-19. This research aims to analyze the implementation, impact and obstacles to restructuring credit on MSMEs at PT. Bank Bengkulu KCP Padang Jaya. This research uses a qualitative method with a case study approach. Data were analyzed using the Miles et al (2014) model which consists of three stages, namely data reduction, data presentation, and drawing conclusions. The research results show that PT. Bank Bengkulu KCP Padang Jaya has carried out credit restructuring in accordance with OJK regulations, by providing relief in the form of deferring interest and principal, reducing interest rates, extending the term, and adding credit facilities to MSME debtors affected by Covid-19. Credit restructuring has a positive impact on debtors and banks, because it can save credit installment costs, allocate funds for other needs, maintain asset quality and liquidity, and reduce the risk of losses due to bad credit. However, the implementation of credit restructuring also experiences several challenges, such as a lack of socialization and public understanding of this policy, limitations in carrying out online applications and verification, as well as policy differences between banks and the OJK, as well as between banks. Suggestions that can be given to increase the effectiveness of restructuring credit are increasing outreach and education to the public, simplifying the application and verification process, providing credit restructuring policies that suit the needs and capabilities of debtors, and being consistent and transparent in implementing credit restructuring policies.